Correlation of platelet‐derived growth factor and thromboxane A2 expression with platelet parameters and coagulation indices in chronic altitude sickness patients. Issue 8 (21st June 2022) - Yin, Yujuan; Geng, Hui; Cui, Sen; Hua‐Ji, Lin
Abstract : New Findings: What is the central question of this study? Is the expression of platelet‐derived growth factor (PDGF) and thromboxane A2 (TXA2) elevated in chronic altitude patients, and are they related to thrombosis in chronic mountain sickness? What is the main finding and its importance? The expression of PDGF and TXA2 in both the bone marrow and the peripheral blood of patients with chronic mountain sickness is elevated, and they are considered to be correlated in the mechanism of thrombosis in the chronic mountain sickness. Abstract: The purpose of this study was to evaluate the expression of platelet‐derived growth factor (PDGF) and thromboxane A2 (TXA2) along with platelet parameters and coagulation indices in chronic mountain sickness (CMS) patients and healthy individuals on the Qinghai‐Tibet Plateau. The levels of PDGF and TXA2 were examined in 22 CMS patients (age, 52.77 ± 9.92 years, haemoglobin, 219 ± 13 g/l) and 25 healthy individuals (age, 47.80 ± 9.78 years, haemoglobin, 146 ± 18 g/l), and the association between platelet parameters and coagulation indices was investigated. Mean platelet volume and fibrinogen degradation product were higher in the CMS compared to the control group ( 10.58 ± 0.83 vs. 8.92 ± 1.61, 7.50 ± 2.15 vs. 4.40 ± 2.51 ), platelet count and plateletcrit were lower in the CMS compared to the control group (0.13 (0.80, 0.16) vs. 0.23 (0.18, 0.24), 109 ± 46 vs. 204 ± 86). The levels of PDGF and TXA2 in the bone marrow and peripheral blood of CMS patients were higher ( P < 0.01) in comparison to the control group. The two factors had no statistically significant relationship with platelet parameters or coagulation indices ( P > 0.159). According to the current findings, platelets in CMS patients were activated, resulting in aberrant coagulation and PDGF and TXA2 expression, which could be due to physiological adjustments to the plateau's high altitude. To summarize, PDGF and TXA2 levels in CMS patients were not correlated with coagulation or platelet parameters, implying that the mechanism behind their increased expression warrants additional investigation.